ANALISIS ARUS TIGA FASA DAYA 197 KVA DENGAN MENGGUNAKAN METODE UJI NORMALITAS KOLMOGOROV-SMIRNOV - Agus Pramono; Teppei Jordy L'ga Tama; Teguh Waluyo (LPPM STMIK STIKOM Indonesia, 2021)
It is necessary to make a monitoring system for the amount of electricity that includes voltage, current, power and the amount of electricity consumption. In this research, carried out in a building that has a 3-phase current with a power of 197 KVA. The analysis used the Kolmogorov-Smirnov normality test method. The Kolmogorov-Smirnov normality test compares the current distribution in the building with the current which is transformed into a Z-score form and is assumed to be normal. In the data analysis, the results of Asymp. Sig. (2-failed) has a value of 0.2. This, this shows the data has been normally distributed